Array Microcell Method (AMCM) for Serial Electroanalysis. Issue 5 (11th February 2020) - Alden, Sasha E.; Siepser, Natasha P.; Patterson, Jacqueline A.; Jagdale, Gargi S.; Choi, Myunghoon; Baker, Lane A.
Abstract: Invited for this month's cover picture is Lane A. Baker's group from the Department of Chemistry at Indiana University (USA). The cover picture shows a method described for addressing electrode arrays through a movable micropipette to contact individual electrodes within an array (electrodes lithographically defined to look like Texas longhorns in this case). Read the full text of the Article at 10.1002/celc.201901976 . Abstract : " The array microcontact method (AMCM) provides a simple yet powerful tool to employ microelectrode arrays for electrochemical and materials studies …" Learn more about the story behind the research featured on the front cover in this issue's Cover Profile. Read the corresponding Article at 10.1002/celc.201901976 .